Pulmonary hydatid cysts: the naturally occurring models for rupture. (September 2016) - Ashour, Mahmoud H; Hajjar, Waseem M; Ishaq, Mohammad; Alamassi, Mohammad; Saleh, Waleed; Al Kattan, Khalid M; Shoukri, Mohamed
Background: Pulmonary hydatid cysts are recognized to have high rate of rupture compared to those in other affected organs. To identify risk factors associated with endobronchial rupture, we prospectively assessed 32 patients with hydatid cysts. There were 21 males and 11 females, with a mean age of 32 ± 15 years (range 9 to 65 years). Methods: All patients undergoing thoracotomies for hydatid cysts were included. Demographic data, site, size, and whether cysts were ruptured or intact, were reviewed. Intraoperatively, bronchial fistula diameters were measured. A stepwise multiple logistic regression model was used to analyze the results. Results: Seventeen (53.1%) patients presented with ruptured cysts (group 1) and 15 with intact cysts (group 2). There was a significant difference in mean fistula diameter between groups: 6.16 ± 2 mm in group 1 vs. 0.34 ± 0.19 mm in group 2 ( p ≤ 0.0001), which was identified as the only significant risk factor associated with cyst rupture. Conclusion: At the fistula site, the intracystic pressure is unopposed, leading to herniation of the endocyst membrane, disruption of its integrity, and rupture. Therefore, we postulate that this scenario in combination with other coexisting factors could be the possible mechanism for cyst rupture in group 1. This concept may also explain the pathogenesis of the high rate of rupture of pulmonary hydatid cysts. Accordingly, we consider these cysts a naturally occurring model for rupture, which should be treated surgically as soon as the diagnosis is made, to avoid complications.